This shattered world : a Starbound novel - Kaufman, Amie (Starbound novel, 2014)
Flynn, leader of the rebellion on Avon, captures Jubilee "Lee" Chase, captain of the forces sent to crush the terraformed planet's rebellious colonists, but later saves her, and the two, caught between sides in a senseless war, flee together.